Joining Palestine to the International Criminal Court is a strategic mistake - Mallem, Youcef; Rebai, Manel Samia (Journal of Human Sciences, 2021)
The crimes committed  by Israel constitute an assault on the foundations and values ​​on which the international community is based, including the criminal responsibility of the individual at the international level, such as the four Geneva Conventions of 1949 and the International Criminal Court of 2002.    The accession of the State of Palestine was supposed to be important  in order to ensure that Israeli criminals are prosecuted by the International Criminal Court.However, the reality has shown facts that prove the opposite and more than that a threat to the Palestinian state and Palestinian leaders, whether they are military or civilian. The problem that I wanted to raise through this article is whether Palestine's accession to the Criminal Court can be considered a strategic mistake.